2021
DOI: 10.1109/access.2021.3117989
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Software Requirements Quality Assurance and Validation: A Systematic Literature Review

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
1
7
0
2
Order By: Relevance
“…The major advantage of the proposed machine learning models versus questionnaire-based approaches is automation, where UX could be evaluated on the fly at any point in time during software development. The UX evaluation could be used as a driving force for requirements analysis and validation [12]. Our study is consistent with the literature review conducted by Almeyda et al [39] that showed that integrating the user experience and agile techniques are essential for requirements analysis.…”
Section: Implications and Limitationssupporting
confidence: 90%
See 1 more Smart Citation
“…The major advantage of the proposed machine learning models versus questionnaire-based approaches is automation, where UX could be evaluated on the fly at any point in time during software development. The UX evaluation could be used as a driving force for requirements analysis and validation [12]. Our study is consistent with the literature review conducted by Almeyda et al [39] that showed that integrating the user experience and agile techniques are essential for requirements analysis.…”
Section: Implications and Limitationssupporting
confidence: 90%
“…As a result, requirements engineers are not fully aware of any early UX software requirements before getting any prototype. Lacking large datasets of software requirements are still a major challenge for proper costeffective and rapid application development [12]. Moreover, the elimination of UX-compliant requirements results in UX neglection in the final product [13] or poor resource planning [14].…”
Section: Introductionmentioning
confidence: 99%
“…They could be called "requirements applied to requirements". Authors have pointed out that consistency, completeness, and correctness are the most used RQ (Atoum et al 2021 andMontgomery et al 2022).…”
Section: Challenges In Early Verification and Validation Of System Re...mentioning
confidence: 99%
“…According to previous studies, the quality of software depends on the correct understanding of the end-users and stakeholders' needs, i.e., the quality of the software requirements (Atoum et al, 2021;Behutiye, Karhapää et al, 2020;Behutiye, Seppänen, et al, 2020;Montgomery et al, 2022;Olsson et al, 2022). Thus, requirements elicitation and specification need to be aligned with business needs in order to meet stakeholder expectations (Ferrari et al, 2021;Karhapää et al, 2021;Montgomery et al, 2022).…”
Section: Introductionmentioning
confidence: 99%